2018
DOI: 10.1021/acs.jpcc.8b06866
|View full text |Cite
|
Sign up to set email alerts
|

A Microscopy Approach to Investigating the Energetics of Small Supported Metal Clusters

Abstract: Metal clusters are partway between molecular and bulk systems and thus exhibit special physical and chemical properties. Atoms can rearrange within a cluster to form different structural isomers. Internal degrees of freedom and the interaction with the supportwhich both are dependent on cluster sizecan promote diffusion across a support. Here, we show how fast scanning tunneling microscopy (FastSTM) can be used to investigate such dynamical behavior of individual clusters on the example of Pdn (1≤n≤19) on a he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Pt clusters containing around 12 atoms were stable up to 400 K . Another study with the same template has shown that Pd single atoms are mobile and coalesce at RT under UHV . A third template, formed by an ultrathin film (0.5 nm) of alumina obtained by high temperature oxidation of a Ni 3 Al­(111) surface, has been discovered by Becker et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pt clusters containing around 12 atoms were stable up to 400 K . Another study with the same template has shown that Pd single atoms are mobile and coalesce at RT under UHV . A third template, formed by an ultrathin film (0.5 nm) of alumina obtained by high temperature oxidation of a Ni 3 Al­(111) surface, has been discovered by Becker et al .…”
Section: Introductionmentioning
confidence: 98%
“…25 Pt clusters containing around 12 atoms were stable up to 400 K. 25 Another study with the same template has shown that Pd single atoms are mobile and coalesce at RT under UHV. 26 A third template, formed by an ultrathin film (0.5 nm) of alumina obtained by high temperature oxidation of a Ni 3 Al(111) surface, has been discovered by Becker et al 27 and used to grow arrays of clusters (Cu, Ag, Au, ...). On this template, Pd clusters containing 5 to 400 atoms are stable up to 600 K under UHV and under CO, at least up to 500 K, allowing the measurement of the desorption energy of CO as a function of cluster size.…”
Section: Introductionmentioning
confidence: 99%
“…This allows, for example, its implementation in experimental setups already optimized for in-situ studies, capable then to work at high temperatures and pressure, as well as in electrochemical environments. In this context, the new FastSTM has been already successfully exploited for the investigation of a variety of dynamical processes occurring at surfaces, such as catalytic reactions [21,22], assembly of supramolecular networks [23] and diffusion of supported metal clusters [24]. These recent results demonstrate the actual possibility to study surface processes at the atomic scale in real-time, providing new insight and understanding on the dynamics occurring in the millisecond time scale.…”
Section: Faststmmentioning
confidence: 95%
“…Um sicherzustellen, dass die Modelle tatsächlich aktive Katalysatoren sind, messen wir deren Reaktivität mit unserem Sniffer-MS an maximal verdünnten Cluster-Proben 7). Sozusagen als Proof-of-concept-Test unserer Fast-STM-Methode haben wir Pd 3 -Cluster auf einem korrugierten, also auf atomarer Ebene welligen Film hexagonalen Bornitrids (h-BN) bei ihrem Tanz innerhalb einer Pore mitverfolgt 8). Wie sich dabei zeigte, diffundieren die Cluster stundenlang im steady state zwischen sechs energetisch äquivalenten Plätzen.…”
unclassified